2011
DOI: 10.1007/s10310-011-0275-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns from different forest generations of Scots pine in Estonia

Abstract: There is strong evidence that climate change alters tree growth in boreal forests. In Estonia, the analysis of ring measurements has been a common method to study growth changes. In this study, annual height growth data from dominant or co-dominant Scots pine (Pinus sylvestris L.) trees were used to develop a growth model for three forest generations. Stem analysis was applied and annual height growth was measured as the distance between whorls, as detected by branch knots of whorls on the split stem surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…In the case of Norway spruce in Norway, comparable trends were obtained by Sharma et al (2012), with the process of amelioration of site conditions also substantially faster in the second half of Tables as well and Tiurin's yield Tables and Bruchwald's site index model the 20th century. A similar trend was also observed in Estonia for height growth of Scots pine (Metslaid et al, 2011). The authors observed significant differences in height growth between generations of trees, stating faster growth of the younger generation of Scots pine trees.…”
Section: Discussionsupporting
confidence: 76%
“…In the case of Norway spruce in Norway, comparable trends were obtained by Sharma et al (2012), with the process of amelioration of site conditions also substantially faster in the second half of Tables as well and Tiurin's yield Tables and Bruchwald's site index model the 20th century. A similar trend was also observed in Estonia for height growth of Scots pine (Metslaid et al, 2011). The authors observed significant differences in height growth between generations of trees, stating faster growth of the younger generation of Scots pine trees.…”
Section: Discussionsupporting
confidence: 76%
“…The H Px increment was greater in younger stands compared to older forests, and this difference was similarly present in both the leaf-off and leaf-on datasets, although the H Px values in the leaf-off dataset were systematically lower. This finding agrees well with existing knowledge of forest growth in Estonia (Kängsepp, Kangur, & Kiviste, 2015;Metslaid et al, 2011). We also found a smaller height increment estimate for the reference stands compared to the stands that were thinned, which can be explained by higher soil fertility in the sample of thinned stands.…”
Section: Discussionsupporting
confidence: 92%
“…The average height increment in young forests (< 20 years) in Estonia is about 0.5 m per year depending on soil fertility (Käng sepp et al, 2015). For older forests, the height increment is usually smaller (0.3 m per year) depending also on soil fertility and forest age (Metslaid et al, 2011). Over four years, i.e.…”
Section: Discussionmentioning
confidence: 99%